AFIRMAREA TOLERANȚEI RELIGIOASE ȘI A IDEII DE UNITATE NAȚIONALĂ ÎN CONTEXTUL ,,CALVINO-TURCISMULUI” (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Affirmation of Religious Tolerance and the Idea of National Unity in the Context of "Calvino-Turkism"In this highly effervent century, with the advent of the Reformation, perhaps the most dear word of that period was reform, with the meaning of renovation, reorganization, not only of the Roman Catholic Church, but also of states, education and politics in general, under the auspices of that strange religion called „Calvino-Turkism,” a bizarre connection, at first glance, between the West and the East, between Islam and Christianity, at the confluence between the two worlds, on these places full of history of Transylvania, the edict of religious tolerance in Turda, which consented to the four accepted religions: Lutheranism, Calvinism, Catholicism and Unitarianism, but also the union of 1600 or the unification of Mihai Viteazu. Both events take place at the same time as giving Transylvania the status of autonomous principality by the Ottoman Empire. Are these pure coincidences of history, or are we able to distinguish certain cause-effect correlations between them? This is the one of the aim of this article.